(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
The integration of technological innovations into accounting practices is pivotal for fostering sustainability in Nigeria’s dynamic business ecosystems. This study investigates how technologies such as cloud accounting, blockchain, and artificial intelligence (AI) can enhance sustainable accounting practices in Cross River State, Nigeria, a region marked by diverse economic activities and environmental priorities. Employing a mixed-methods approach, primary data were collected via surveys and interviews with 200 accountants and business managers from 50 firms in Calabar and Ugep. Findings indicate that cloud accounting improves efficiency and transparency, blockchain enhances financial security, and AI streamlines data analysis, yet challenges like high implementation costs and limited digital literacy persist. Demographic analysis reveals participants were 55% male and 45% female, predominantly aged 25–40, with varying technology adoption levels. The study highlights the need for tailored training, policy support, and infrastructure investment to align technological advancements with sustainable development goals. Recommendations include fostering public-private partnerships, subsidizing technology adoption, and embedding sustainability metrics in accounting curricula. This research positions Cross River State as a potential model for sustainable accounting in Nigeria, contributing to global discourse on technology-driven financial practices.